SINTESIS SISTEM KENDALI DISIPATIF DENGAN MENGGUNAKAN PENDEKATAN PERTIDAKSAMAAN MATRIKS LINIER - Ida W.D., Aciek
Abstract : Using mathematical abstractions of the notions of physical power and energy, the concept of energy dissipation has been employed to develop sufficient conditions for stability with dissipative systems. Numerous stability results in the literature such as small gain conditions, passivity conditions, and sector conditions for stability follow naturally as special cases from this framework of dissipative systems. Time domain characterizations of dissipative linear time invariant (LTI) systems is referred to as the dissipativity lemma, since it is a generalization of the Kalman-Yakubovich lemma (or positive realness lemma) for positive real systems, and the bounded realness lemma for gain bounded systems. The conditions of the dissipativity lemma can be equivalently expressed in term of a linear matrix inequality (LMI). The LMI characterization of dissipative LTI systems is very important in application of these results for tight characterization of uncertain plants in terms of dissipativity. LMI characterizations of gain bounded, positive real, and sector bounded systems follow directly from the LMI characterization of dissipative LTI systems by substituting their respective power functions. On this research, the synthesis of dissipative control systems begins with the dissipative theorem for LTI systems. The characterizations of LMI dissipative consists of two matrix inequalities is changed into a three matrix inequalities system using matrix decomposition and Schur complement. Thus, using lemma and theorem which occurs on the LMI systems. For the material study, the design of H00 controller, the controlling mobile dynamics lateral-directional of airplane N250 supported by MATLAB software, especially LMI Control Toolbox, produced by the MATH WORKS; Inc. The work shows that the controller has been sufficient the truth of the theorem and able to control the plant (airplane) with the result that the plant gives good reaction. This conditions shows a good prospect for developing the design of dissipative systems.